Photoelectric composite material, preparation method and application thereof

Through the photoelectro-catalytic technology of FTO/Au/MoSe2/WSe2/CuGaSe/Bi2O3-Se composite photoelectric materials, the problems of low energy efficiency and low product selectivity during carbon dioxide conversion are solved, and the CO2 reduction is achieved efficient and selective. The methanol yield is high and the material is stable.

CN119307970APending Publication Date: 2025-01-14杜宏财
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411488494.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The prior art has problems of inefficient energy efficiency and low product selectivity when converting carbon dioxide into valuable chemical fuels, making it difficult to efficiently and selectively generate specific products.

Method used

FTO/Au/MoSe2/WSe2/CuGaSe/Bi2O3-Se composite photoelectric material is used as heterojunction material. CO2 is reduced by photoelectric catalytic, carriers are excitated by solar light and migrated under the external potential field to achieve efficient conversion of CO2.

Benefits of technology

The efficiency and selectivity of CO2 reduction are improved, the methanol produced reaches 382 nmol/cm2, and the material is stable and has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a photoelectric composite material as well as a preparation method and application thereof, the material is an FTO / Au / MoSe2 / WSe2 / CuGaSe / Bi2O3-Se composite photoelectric material, and the prepared photoelectric material has the best carbon dioxide reduction performance and the methanol yield of 382 nmol / cm < 2 > under the conditions that a relatively low bias voltage (-1.0 V, vs.SCE) is applied and the light intensity is 100 mW / cm < 2 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of heterojunction optoelectronic composite materials, and in particular to an optoelectronic composite material, a preparation method and an application thereof in photoelectric reduction of CO2 to prepare alcohol substances. Background Art

[0002] Starting from the realization of sustainable development, the total emission of CO2 can be reduced by changing consumption patterns. For example, traditional fossil resources can be turned to abundant and renewable low-carbon energy such as solar energy and wind energy. For most of human history, the level of CO2 in the atmosphere has been almost constant at around 280 ppm. However, in the past 60 years, the concentration of CO2 in the world's atmosphere has increased by about 30%, and its concentration value has exceeded 410 ppm, which is more than 1.1 times the upper limit of ecological safety of 350 ppm. Due to the large-scale use of fossil fuels in the process of industrialization, the circulation chain in which these human activities participate offsets the positive contribution of photosynthesis in nature and breaks the global carbon balance. The various earth ecological and environmental problems caused by global warming, glacier melting, sea level rise, ocean acidification, biodiversity, etc. have in turn restricted human survival and economic development. In this case, reducing carbon emissions through carbon neutrality is the best way to achieve the transition of human society from the "fossil age" to a sustainable low-carbon economy. Compared with the currently used carbon capture, storage and separation methods, producing valuable hydrocarbon fuels using CO2 as raw material is the greenest and most realistic way to achieve a carbon-neutral cycle.

[0003] CO2 is a linear molecule containing two C=O bonds with triple bond characteristics and has high thermodynamic stability. So far, the methods for converting and utilizing CO2 mainly include two categories: physical methods and chemical methods. Generally speaking, physical strategies such as geological and deep-sea storage are generally limited by high economic costs, high space requirements, and complex processes. Converting CO2 into valuable chemical fuels through chemical methods such as hydrogenation, thermochemistry, photocatalysis, electrocatalysis, and photoelectrocatalysis is an effective strategy for regulating carbon balance and achieving sustainable development strategies. However, CO2 molecules are extremely stable and the C=O bonds are very strong, so it is generally difficult to efficiently convert them into reduced products. In order to activate them, it is usually necessary to inject enough energy, but this often leads to low energy efficiency. For example, classical gas-solid thermal catalysis generally requires harsh conditions to obtain relatively satisfactory CO2 conversion rates, at the cost of high energy costs and uncontrollable product selectivity. Therefore, converting and utilizing CO2 through chemical methods is expected to become a realistic strategy.

[0004] The carbon dioxide reduction reaction is a highly complex process. Generally, through the transfer of multiple protons and electrons, different gas and liquid products can be obtained, such as carbon monoxide (CO), methane (CH4), methanol (CH3OH), formic acid (HCOOH), ethylene (C2H4), ethanol (CH3CH2OH), etc. However, the redox potentials of the above-mentioned reduction products are relatively close, which makes it difficult to selectively generate a specific product by CO2 reduction. Therefore, how to utilize CO2 efficiently, with high conversion rate and high product selectivity is a key issue.

[0005] Since both electrocatalysis and photocatalysis have certain limitations in the practical application of CO2 reduction, researchers have combined these two technologies to develop a new photoelectrocatalysis (PEC) method for CO2RR. This PEC-CO2RR method refers to the process in which a semiconductor photoelectrode generates photoelectrons under the excitation of a light source, and then the photoelectrons migrate to the electrode surface under the guidance of an external potential field to catalytically reduce CO2. Studies have shown that converting CO2 into valuable chemicals through photoelectrocatalysis is one of the most efficient methods for converting CO2 using renewable energy. The whole process can not only reduce external energy input, but also achieve efficient utilization of low-carbon, clean and sustainable energy. Compared with the single electrocatalytic CO2 reduction process, photoelectrocatalysis can use sunlight as an energy source to excite the generation of carriers, and then participate in the redox reaction, and finally achieve CO2 reduction with lower energy consumption. Compared with single photocatalysis, photoelectrocatalysis can also achieve rapid electron transfer and reduce CO2 at a lower potential, greatly improving the reduction efficiency. Summary of the invention

[0006] The present invention provides a FTO / Au / MoSe2 / WSe2 / CuGaSe / Bi2O3-Se composite photoelectric material. As a heterojunction material, the composite material has strong photoelectrochemical performance and carbon dioxide reduction performance, and has excellent catalytic performance and good stability, and has good application prospects.

[0007] A method for preparing a photoelectric composite material comprises the following steps: (1) FTO glass surface pretreatment: The FTO glass was immersed in an ultrasonic-assisted degreasing solution, then rinsed with ethanol and deionized water in sequence, and then dried with nitrogen; (2) Evaporation of Au layer, the thickness of the Au layer is 10-15nm; (3) Preparing a MoSe2 suspension and coating a MoSe2 layer: adding 1-2 mM sodium molybdate, 2-2.5 mM selenium powder, 1-1.5 mM sodium borohydride, and 10-20 mL ethanol to deionized water, stirring thoroughly, transferring to a hydrothermal reactor, and subjecting the mixture to a hydrothermal reaction at 170-190°C for 24-30 h, cooling, and filtering to obtain a solid substance, stirring the solid substance with 10-25 mL polyacrylic acid for 1-2 h, and allowing the mixture to stand for 20-24 h, and then coating the Au layer prepared in step (2) with an immersion pull-up method at a pull-up speed of 10-15 mm / s for 150-200 s, and then drying with nitrogen at 50-60°C to obtain a MoSe2 layer; (4) Preparing a WSe2 suspension and coating a WSe2 layer: adding 1-2 mM sodium tungstate, 2-4 mM selenium powder, 1.3-2 mM sodium borohydride, and 60-100 mL DMF to deionized water, stirring thoroughly, transferring to a hydrothermal reactor, and subjecting to a hydrothermal reaction at 180-200° C. for 24-30 h, cooling, and filtering to obtain a solid substance, stirring the solid substance with 10-25 mL polyacrylic acid for 1-2 h, allowing it to stand for 20-24 h, and then coating the Au layer prepared in step (2) with an immersion pull-up method at a pull-up speed of 10-15 mm / s for 200-300 s, and then drying with nitrogen at 50-60° C. to obtain a WSe2 layer; (5) Constant potential deposition of CuGaSe layer: The FTO / Au / MoSe2 / WSe2 prepared in step (4) is used as the working electrode and placed on the Cu 2+ : Ga 3+ :SeO3 2- In a solution of 1.6mmol / L:1.5mmol / L:4mmol / L, 0.5 mol / L sodium citrate is used as a complexing agent and 1.0 mol / L sodium sulfate is used as an electrolyte, HCl is used to adjust the pH value to between 1.8 and 2.0, and a single deposition is performed at -0.5V for 10s at a constant potential under stirring conditions, and the cumulative deposition is repeated 15 times to obtain a CuGaSe layer; (6) Prepare a selenium-modified bismuth oxide electrolyte and electrodeposit a Se-Bi2O3 layer: the electrolyte includes 4.85mmol / L bismuth nitrate, 0.9mmol / L sodium selenate, 0.2mmol / L acetic acid and deionized water, use the FTO / Au / MoSe2 / WSe2 / CuGaSe prepared in step (5) as the working electrode, a platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode, deposit for 30-60min at a constant potential of -0.7V, dry it, take it out, and dry it in a 5vol.% oxygen-nitrogen mixed gas at a drying temperature of 70-80°C for 10-15h to finally obtain the desired optoelectronic composite material.

[0008] Further, the optoelectronic composite material is, from bottom to top, an FTO substrate, a vapor-deposited Au layer, a MoSe2 coating, a WSe2 coating, a CuGaSe electrodeposited layer, and a Se-Bi2O3 electrodeposited layer, see the attached Figure 3 .

[0009] Furthermore, the thickness of MoSe2 is 70-80 μm.

[0010] Furthermore, the thickness of WSe2 is 100-130 μm.

[0011] Furthermore, the thickness of CuGaSe is 100-130 μm.

[0012] Furthermore, the thickness of Se-Bi2O3 is 90-120 μm.

[0013] Furthermore, the composite material is used for photoelectrocatalytic reduction of carbon dioxide electrode.

[0014] Beneficial technical effects: The present invention provides a FTO / Au / MoSe2 / WSe2 / CuGaSe / Bi2O3-Se composite photoelectric material. As a heterojunction material, the composite material has strong photoelectrochemical properties and carbon dioxide reduction properties, and has excellent catalytic properties and good stability, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Attached Figure 1 Photoelectrocatalytic activity test diagram of Example 2 and Comparative Example 1.

[0016] Attached Figure 2 TEM image of the multilayer optoelectronic composite material obtained in Example 2.

[0017] Attached Figure 3 Photoelectric stability test chart of the multilayer photoelectric composite material obtained in Example 2. DETAILED DESCRIPTION Example 1

[0018] A method for preparing a photoelectric composite material comprises the following steps: (1) FTO glass surface pretreatment: The FTO glass was immersed in an ultrasonic-assisted degreasing solution, then rinsed with ethanol and deionized water in sequence, and then dried with nitrogen.

[0019] (2) Evaporation of Au layer, the thickness of the Au layer is 10-15nm.

[0020] (3) Preparing a MoSe2 suspension and coating a MoSe2 layer: adding 1 mM sodium molybdate, 2 mM selenium powder, 1 mM sodium borohydride, and 10 mL of ethanol to deionized water, stirring thoroughly, transferring to a hydrothermal reactor, and subjecting to a hydrothermal reaction at 170°C for 24 h, cooling, and filtering to obtain a solid substance, stirring the solid substance with 10 mL of polyacrylic acid for 1-2 h, allowing it to stand for 20 h, and then coating the Au layer prepared in step (2) using an immersion pulling method at a pulling speed of 10 mm / s for 150 s, and then drying with nitrogen at 50°C to obtain a MoSe2 layer.

[0021] (4) Prepare WSe2 suspension and apply WSe2 layer: add 1mM sodium tungstate, 2mM selenium powder, 1.3mM sodium borohydride and 60mL DMF into deionized water, stir well, transfer to a hydrothermal reactor, react at 180°C for 24h, cool, filter to obtain solid substance, mix the solid substance with 10mL polyacrylic acid by stirring for 1h, let stand for 20h, and then use immersion pulling method to coat the coating prepared in step (3) at a pulling speed of 10mm / s for 200s, and then dry with nitrogen at 50°C to obtain WSe2 layer.

[0022] (5) Constant potential deposition of CuGaSe layer: The FTO / Au / MoSe2 / WSe2 prepared in step (4) is used as the working electrode and placed on the Cu 2+ : Ga 3+ :SeO3 2- In solutions of 1.6mmol / L:1.5mmol / L:4mmol / L respectively, 0.5 mol / L sodium citrate was used as a complexing agent and 1.0 mol / L sodium sulfate was used as an electrolyte. HCl was used to adjust the pH value to 1.8. Under stirring conditions, a single deposition was performed at -0.5V at a constant potential for 10s. The deposition was repeated 15 times to obtain a CuGaSe layer.

[0023] (6) Prepare a selenium-modified bismuth oxide electrolyte and electrodeposit a Se-Bi2O3 layer: the electrolyte includes 4.85mmol / L bismuth nitrate, 0.9mmol / L sodium selenate, 0.2mmol / L acetic acid and deionized water, use the FTO / Au / MoSe2 / WSe2 / CuGaSe prepared in step (5) as the working electrode, a platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode, deposit for 30 minutes at a constant potential of -0.7V, dry it, take it out, and dry it in a 5vol.% oxygen-nitrogen mixed gas at a drying temperature of 70°C for 10 hours to finally obtain the desired optoelectronic composite material. Example 2

[0024] A method for preparing a photoelectric composite material comprises the following steps: (1) FTO glass surface pretreatment: The FTO glass was immersed in an ultrasonic-assisted degreasing solution, then rinsed with ethanol and deionized water in sequence, and then dried with nitrogen.

[0025] (2) Evaporation of Au layer, the thickness of the Au layer is 10-15nm.

[0026] (3) Preparing a MoSe2 suspension and coating a MoSe2 layer: adding 1.5 mM sodium molybdate, 2.25 mM selenium powder, 1.25 mM sodium borohydride, and 15 mL of ethanol to deionized water, stirring thoroughly, transferring to a hydrothermal reactor, and subjecting to a hydrothermal reaction at 180°C for 27 h, cooling, and filtering to obtain a solid substance, stirring the solid substance with 17.5 mL of polyacrylic acid for 1.5 h, allowing it to stand for 22 h, and then coating the Au layer prepared in step (2) with an immersion pulling method at a pulling speed of 12.5 mm / s for 175 s, and then drying with nitrogen at 55°C to obtain a MoSe2 layer.

[0027] (4) Prepare WSe2 suspension and apply WSe2 layer: add 1.5mM sodium tungstate, 3mM selenium powder, 1.65mM sodium borohydride and 80mL DMF into deionized water, stir well, transfer to a hydrothermal reactor, react at 190°C for 27h, cool, filter to obtain solid material, mix the solid material with 17.5mL polyacrylic acid by stirring for 1.5h, let stand for 22h, and then use immersion pulling method to apply on the coating prepared in step (3) at a pulling speed of 12.5mm / s for 250s, and then dry with nitrogen at 55°C to obtain WSe2 layer.

[0028] (5) Constant potential deposition of CuGaSe layer: The FTO / Au / MoSe2 / WSe2 prepared in step (4) is used as the working electrode and placed on the Cu 2+ : Ga 3+ :SeO3 2- In solutions of 1.6mmol / L:1.5mmol / L:4mmol / L respectively, 0.5 mol / L sodium citrate was used as a complexing agent and 1.0 mol / L sodium sulfate was used as an electrolyte. HCl was used to adjust the pH value to 1.9. Under stirring conditions, a single deposition was performed at -0.5V at a constant potential for 10s. The deposition was repeated 15 times to obtain a CuGaSe layer.

[0029] (6) Prepare a selenium-modified bismuth oxide electrolyte and electrodeposit a Se-Bi2O3 layer: the electrolyte includes 4.85 mmol / L bismuth nitrate, 0.9 mmol / L sodium selenate, 0.2 mmol / L acetic acid and deionized water, use the FTO / Au / MoSe2 / WSe2 / CuGaSe prepared in step (5) as the working electrode, a platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode. Deposit for 45 min at a constant potential of -0.7 V, dry it, take it out, and dry it in a 5 vol.% oxygen-nitrogen mixture at a drying temperature of 75°C for 12.5 h to finally obtain the desired optoelectronic composite material. Example 3

[0030] A method for preparing a photoelectric composite material comprises the following steps: (1) FTO glass surface pretreatment: The FTO glass was immersed in an ultrasonic-assisted degreasing solution, then rinsed with ethanol and deionized water in sequence, and then dried with nitrogen.

[0031] (2) Evaporation of Au layer, the thickness of the Au layer is 10-15nm.

[0032] (3) Preparing a MoSe2 suspension and coating a MoSe2 layer: adding 2 mM sodium molybdate, 2.5 mM selenium powder, 1.5 mM sodium borohydride, and 20 mL of ethanol to deionized water, stirring thoroughly, transferring to a hydrothermal reactor, and subjecting the mixture to a hydrothermal reaction at 190°C for 30 h, cooling, and filtering to obtain a solid substance, stirring the solid substance with 25 mL of polyacrylic acid for 2 h, allowing the mixture to stand for 24 h, and then coating the coating prepared in step (3) using an immersion pulling method at a pulling speed of 15 mm / s for 200 s, and then drying with nitrogen at 60°C to obtain a MoSe2 layer.

[0033] (4) Prepare WSe2 suspension and apply WSe2 layer: add 1mM sodium tungstate, 2mM selenium powder, 1.3mM sodium borohydride and 60mL DMF into deionized water, stir well, transfer to a hydrothermal reactor, and react at 180°C for 24h, cool, filter and obtain solid material, mix the solid material with 10mL polyacrylic acid by stirring for 1-2h, let stand for 20-24h, and then use immersion pulling method to coat the Au layer prepared in step (2) at a pulling speed of 10mm / s for 200s, and then dry with nitrogen at 50°C to obtain WSe2 layer.

[0034] (5) Constant potential deposition of CuGaSe layer: The FTO / Au / MoSe2 / WSe2 prepared in step (4) is used as the working electrode and placed on the Cu 2+ : Ga 3+ :SeO3 2-In solutions of 1.6mmol / L:1.5mmol / L:4mmol / L respectively, 0.5 mol / L sodium citrate is used as a complexing agent and 1.0 mol / L sodium sulfate is used as an electrolyte. HCl is used to adjust the pH value between 1.8 and 2.0. Under stirring conditions, a single deposition is carried out at -0.5V at a constant potential for 10s. The deposition is repeated 15 times to obtain a CuGaSe layer.

[0035] (6) Prepare a selenium-modified bismuth oxide electrolyte and electrodeposit a Se-Bi2O3 layer: the electrolyte includes 4.85mmol / L bismuth nitrate, 0.9mmol / L sodium selenate, 0.2mmol / L acetic acid and deionized water, use the FTO / Au / MoSe2 / WSe2 / CuGaSe prepared in step (5) as the working electrode, a platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode, deposit for 60min at a constant potential of -0.7V, dry it, take it out, and dry it in a 5vol.% oxygen-nitrogen mixed gas at a drying temperature of 80°C for 15h to finally obtain the desired optoelectronic composite material.

[0036] Comparative Example 1 A method for preparing an optoelectronic composite material comprises the following steps: (1) FTO glass surface pretreatment: The FTO glass was immersed in an ultrasonic-assisted degreasing solution, then rinsed with ethanol and deionized water in sequence, and then dried with nitrogen.

[0037] (2) Evaporation of Au layer, the thickness of the Au layer is 10-15nm.

[0038] (3) Preparation of WSe2 suspension and coating of WSe2 layer: 1.5 mM sodium tungstate, 3 mM selenium powder, 1.65 mM sodium borohydride and 80 mL DMF were added to deionized water, stirred thoroughly, and then transferred to a hydrothermal reactor for hydrothermal reaction at 190 °C for 27 h. The solid was then cooled and filtered to obtain a solid substance. The solid substance was mixed with 17.5 mL polyacrylic acid and stirred for 1.5 h, and allowed to stand for 22 h. The solid was then coated on the Au layer prepared in step (2) by the immersion pulling method at a pulling speed of 12.5 mm / s for 250 s, and then dried with nitrogen at 55 °C to obtain a WSe2 layer.

[0039] (4) Preparing a MoSe2 suspension and coating a MoSe2 layer: 1.5 mM sodium molybdate, 2.25 mM selenium powder, 1.25 mM sodium borohydride, and 15 mL of ethanol were added to deionized water, stirred thoroughly, and then transferred to a hydrothermal reactor for a hydrothermal reaction at 180°C for 27 h. The solid was then cooled and filtered to obtain a solid substance. The solid substance was mixed with 17.5 mL of polyacrylic acid and stirred for 1.5 h, and allowed to stand for 22 h. The solid was then coated on the Au layer prepared in step (3) by an immersion pulling method at a pulling speed of 12.5 mm / s for 175 s, and then dried with nitrogen at 55°C to obtain a MoSe2 layer.

[0040] (5) Constant potential deposition of CuGaSe layer: The working electrode prepared in step (4) is placed on the Cu 2+ : Ga 3+ :SeO3 2- In solutions of 1.6mmol / L:1.5mmol / L:4mmol / L respectively, 0.5 mol / L sodium citrate is used as a complexing agent and 1.0 mol / L sodium sulfate is used as an electrolyte. HCl is used to adjust the pH value to 1.9. Under stirring conditions, a single deposition is performed at -0.5V at a constant potential for 10s. The deposition is repeated 15 times to obtain a CuGaSe layer.

[0041] (6) Prepare a selenium-modified bismuth oxide electrolyte and electrodeposit a Se-Bi2O3 layer: the electrolyte includes 4.85mmol / L bismuth nitrate, 0.9mmol / L sodium selenate, 0.2mmol / L acetic acid and deionized water. The electrode prepared in step (5) is used as the working electrode, the platinum mesh is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode. The electrode is deposited at a constant potential of -0.7V for 45min, and then air-dried and taken out. The electrode is dried in a 5vol.% oxygen-nitrogen mixture at a drying temperature of 75°C for 12.5h to obtain the desired optoelectronic composite material.

[0042] Comparative Example 2 A method for preparing a photoelectric composite material comprises the following steps: (1) FTO glass surface pretreatment: The FTO glass was immersed in an ultrasonic-assisted degreasing solution, then rinsed with ethanol and deionized water in sequence, and then dried with nitrogen; (2) Evaporation of Au layer, the thickness of the Au layer is 10-15nm.

[0043] (3) Prepare a selenium-modified bismuth oxide electrolyte and electrodeposit a Se-Bi2O3 layer: the electrolyte includes 4.85mmol / L bismuth nitrate, 0.9mmol / L sodium selenate, 0.2mmol / L acetic acid and deionized water. The electrode prepared in step (2) is used as the working electrode, the platinum mesh is used as the counter electrode, and the saturated calomel electrode is used as the reference electrode. The electrode is deposited at a constant potential of -0.7V for 45min, air-dried, and dried in a 5vol.% oxygen-nitrogen mixed gas at a drying temperature of 75°C for 12.5h to finally obtain the desired optoelectronic composite material.

[0044] (4) Preparing a MoSe2 suspension and coating a MoSe2 layer: 1.5 mM sodium molybdate, 2.25 mM selenium powder, 1.25 mM sodium borohydride, and 15 mL of ethanol were added to deionized water, stirred thoroughly, and then transferred to a hydrothermal reactor for a hydrothermal reaction at 180°C for 27 h. The solid was then cooled and filtered to obtain a solid substance. The solid substance was mixed with 17.5 mL of polyacrylic acid and stirred for 1.5 h, and allowed to stand for 22 h. The solid was then coated on the Au layer prepared in step (3) by an immersion pulling method at a pulling speed of 12.5 mm / s for 175 s, and then dried with nitrogen at 55°C to obtain a MoSe2 layer.

[0045] (5) Prepare WSe2 suspension and apply WSe2 layer: add 1.5mM sodium tungstate, 3mM selenium powder, 1.65mM sodium borohydride and 80mL DMF into deionized water, stir well, transfer to a hydrothermal reactor, react at 190°C for 27h, cool, filter and obtain solid substance, mix the solid substance with 17.5mL polyacrylic acid by stirring for 1.5h, let stand for 22h, and then use immersion pulling method to coat the layer prepared in step (4) at a pulling speed of 12.5mm / s for 250s, and then dry with nitrogen at 55°C to obtain WSe2 layer.

[0046] (6) Constant potential deposition of CuGaSe layer: The working electrode prepared in step (4) is placed on the Cu 2+ : Ga 3+ :SeO3 2- In solutions of 1.6mmol / L:1.5mmol / L:4mmol / L respectively, 0.5 mol / L sodium citrate is used as a complexing agent and 1.0 mol / L sodium sulfate is used as an electrolyte. HCl is used to adjust the pH value to 1.9. Under stirring conditions, a single deposition is performed at -0.5V at a constant potential for 10s. The deposition is repeated 15 times to obtain a CuGaSe layer.

[0047] Comparative Example 3 A method for preparing a photoelectric composite material comprises the following steps: (1) FTO glass surface pretreatment: The FTO glass was immersed in an ultrasonic-assisted degreasing solution, then rinsed with ethanol and deionized water in sequence, and then dried with nitrogen.

[0048] (2) Evaporation of Au layer, the thickness of the Au layer is 10-15nm.

[0049] (3) Preparing a MoSe2 suspension and coating a MoSe2 layer: adding 1.5 mM sodium molybdate, 2.25 mM selenium powder, 1.25 mM sodium borohydride, and 15 mL of ethanol to deionized water, stirring thoroughly, transferring to a hydrothermal reactor, and subjecting to a hydrothermal reaction at 180°C for 27 h, cooling, and filtering to obtain a solid substance, stirring the solid substance with 17.5 mL of polyacrylic acid for 1.5 h, allowing it to stand for 22 h, and then coating the Au layer prepared in step (2) with an immersion pulling method at a pulling speed of 12.5 mm / s for 175 s, and then drying with nitrogen at 55°C to obtain a MoSe2 layer.

[0050] (4) Prepare WSe2 suspension and apply WSe2 layer: add 1.5mM sodium tungstate, 3mM selenium powder, 1.65mM sodium borohydride and 80mL DMF into deionized water, stir well, transfer to a hydrothermal reactor, react at 190°C for 27h, cool, filter and obtain solid substance, mix the solid substance with 17.5mL polyacrylic acid by stirring for 1.5h, let stand for 22h, and then use immersion pulling method to coat the layer prepared in step (3) at a pulling speed of 12.5mm / s for 250s, and then dry with nitrogen at 55°C to obtain WSe2 layer.

[0051] (5) Prepare a selenium-modified bismuth oxide electrolyte and electrodeposit a Se-Bi2O3 layer: the electrolyte includes 4.85 mmol / L bismuth nitrate, 0.9 mmol / L sodium selenate, 0.2 mmol / L acetic acid and deionized water, use the FTO / Au / MoSe2 / WSe2 / CuGaSe prepared in step (4) as the working electrode, a platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode, deposit for 45 min at a constant potential of -0.7 V, dry it, take it out, and dry it in a 5 vol.% oxygen-nitrogen mixture at a drying temperature of 75°C for 12.5 h to finally obtain the desired optoelectronic composite material.

[0052] (6) Constant potential deposition of CuGaSe layer: The working electrode prepared in step (5) is placed on the Cu 2+ : Ga 3+ :SeO3 2-In solutions of 1.6mmol / L:1.5mmol / L:4mmol / L respectively, 0.5 mol / L sodium citrate was used as a complexing agent and 1.0 mol / L sodium sulfate was used as an electrolyte. HCl was used to adjust the pH value to 1.9. Under stirring conditions, a single deposition was performed at -0.5V at a constant potential for 10s. The deposition was repeated 15 times to obtain a CuGaSe layer.

[0053] Comparative Example 4 A method for preparing an optoelectronic composite material comprises the following steps: (1) FTO glass surface pretreatment: The FTO glass was immersed in an ultrasonic-assisted degreasing solution, then rinsed with ethanol and deionized water in sequence, and then dried with nitrogen.

[0054] (2) Evaporation of Au layer, the thickness of the Au layer is 10-15nm.

[0055] (3) Prepare a selenium-modified bismuth oxide electrolyte and electrodeposit a Se-Bi2O3 layer: the electrolyte includes 4.85mmol / L bismuth nitrate, 0.9mmol / L sodium selenate, 0.2mmol / L acetic acid and deionized water, use the FTO / Au / MoSe2 / WSe2 / CuGaSe prepared in step (2) as the working electrode, a platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode, deposit for 45min at a constant potential of -0.7V, dry it, take it out, and dry it in a 5vol.% oxygen-nitrogen mixed gas at a drying temperature of 75°C for 12.5h to finally obtain the desired optoelectronic composite material.

[0056] (4) Preparing a MoSe2 suspension and coating a MoSe2 layer: 1.5 mM sodium molybdate, 2.25 mM selenium powder, 1.25 mM sodium borohydride, and 15 mL of ethanol were added to deionized water, stirred thoroughly, and then transferred to a hydrothermal reactor for hydrothermal reaction at 180°C for 27 h. The solid was then cooled and filtered to obtain a solid substance. The solid substance was mixed with 17.5 mL of polyacrylic acid and stirred for 1.5 h, and allowed to stand for 22 h. The solid was then coated on the layer prepared in step (3) by an immersion pulling method at a pulling speed of 12.5 mm / s for 175 s, and then dried with nitrogen at 55°C to obtain a MoSe2 layer.

[0057] (5) Preparation of WSe2 suspension and coating of WSe2 layer: 1.5 mM sodium tungstate, 3 mM selenium powder, 1.65 mM sodium borohydride and 80 mL DMF were added to deionized water, stirred thoroughly, and then transferred to a hydrothermal reactor for hydrothermal reaction at 190 °C for 27 h. The solid was then cooled and filtered to obtain a solid substance. The solid substance was mixed with 17.5 mL polyacrylic acid and stirred for 1.5 h, and allowed to stand for 22 h. The solid was then coated on the layer prepared in step (2) by the immersion pulling method at a pulling speed of 12.5 mm / s for 250 s, and then dried with nitrogen at 55 °C to obtain a WSe2 layer.

[0058] (6) Constant potential deposition of CuGaSe layer: The working electrode prepared in step (5) is placed on the Cu 2+ : Ga 3+ :SeO3 2- In solutions of 1.6mmol / L:1.5mmol / L:4mmol / L respectively, 0.5 mol / L sodium citrate is used as a complexing agent and 1.0 mol / L sodium sulfate is used as an electrolyte. HCl is used to adjust the pH value to 1.9. Under stirring conditions, a single deposition is performed at -0.5V at a constant potential for 10s. The deposition is repeated 15 times to obtain a CuGaSe layer.

[0059] Photoelectrocatalytic activity test: The photoelectrocatalytic reduction of CO2 test is carried out in a high temperature resistant and airtight all-PTFE H-type electrolytic cell. The H-type electrolytic cell has two compartments, namely the cathode and the cation, separated by a Nafion-117 ion exchange membrane. It was carried out under a three-electrode test system, in which the prepared material was used as the working electrode, the saturated potassium chloride electrode was used as the reference electrode, and the foam copper was used as the counter electrode. 100 mL of 0.5 M KHCO3 electrolyte was used in the cathode to reduce CO2, and the foam copper needed to be completely immersed in the electrolyte. 0.2 M Na2SO4 electrolyte was used in the cation, and the prepared material also needed to be completely immersed in the solution. Before the reaction started, high-purity CO2 (99.99%) was used to blow the electrolyte in the cathode for about 20 minutes to completely remove oxygen and make CO2 saturated in the electrolyte. The light intensity of the xenon lamp was then adjusted to 100 mW / cm 2 , and the photoelectrocatalysis was carried out at a constant potential of 1.0 V (vs. KCl) for 4 hours. Finally, the liquid solution after the reaction was collected from the cathode chamber, and the liquid product was analyzed by nuclear magnetic resonance spectrometer.

[0060] The photoelectrode prepared by the present invention is used as a working electrode, that is, as an anode photoelectrode. Under a bias voltage of 1.0 V, the photoelectrode has the best carbon dioxide reduction performance, and the methanol production can reach 382 nmol / cm 2 By adjusting the relationship between the layers, the methanol yields of Comparative Example 1: FTO / Au / WSe2 / MoSe2 / CuGaSe / Bi2O3-Se; Comparative Example 2: FTO / Au / CuGaSe / MoSe2 / WSe2 / Bi2O3-Se; Comparative Example 3: FTO / Au / MoSe2 / WSe2 / Bi2O3-Se / CuGaSe / ; Comparative Example 4: FTO / Au / Bi2O3-Se / MoSe2 / WSe2 / CuGaSe / were 257nmol / cm 2 , 221nmol / cm 2 , 204nmol / cm 2 、168nmol / cm 2 The catalytic activity decreases successively. The possible reason is that the energy driven by the heterojunction to separate the electron-hole pairs is insufficient to suppress their recombination, resulting in the methanol production not reaching the level of Example 2. For details, see the attached Figure 1 In addition, the stability test of the composite photoelectric in Example 2 is carried out, as shown in the attached Figure 2 As shown, it indicates that the composite photoelectrode has good stability.

[0061] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a photoelectric composite material, characterized in that The steps include: (1) FTO glass surface pretreatment: The FTO glass was immersed in an ultrasonic-assisted degreasing solution, then rinsed with ethanol and deionized water in sequence, and then dried with nitrogen; (2) Evaporation of Au layer, the thickness of the Au layer is 10-15nm; (3) Preparing a MoSe2 suspension and coating a MoSe2 layer: adding 1-2 mM sodium molybdate, 2-2.5 mM selenium powder, 1-1.5 mM sodium borohydride, and 10-20 mL ethanol to deionized water, stirring thoroughly, transferring to a hydrothermal reactor, and subjecting the mixture to a hydrothermal reaction at 170-190°C for 24-30 h, cooling, and filtering to obtain a solid substance, stirring the solid substance with 10-25 mL polyacrylic acid for 1-2 h, and allowing the mixture to stand for 20-24 h, and then coating the Au layer prepared in step (2) with an immersion pull-up method at a pull-up speed of 10-15 mm / s for 150-200 s, and then drying with nitrogen at 50-60°C to obtain a MoSe2 layer; (4) Preparing a WSe2 suspension and coating a WSe2 layer: adding 1-2 mM sodium tungstate, 2-4 mM selenium powder, 1.3-2 mM sodium borohydride, and 60-100 mL DMF to deionized water, stirring thoroughly, transferring to a hydrothermal reactor, and hydrothermally reacting at 180-200° C. for 24-30 h, cooling, and filtering to obtain a solid substance, stirring the solid substance with 10-25 mL polyacrylic acid for 1-2 h, and standing for 20-24 h, and then coating the coating prepared in step (3) by an immersion pulling method at a pulling speed of 10-15 mm / s for 200-300 s, and then drying with nitrogen at 50-60° C. to obtain a WSe2 layer; (5) Constant potential deposition of CuGaSe layer: The FTO / Au / MoSe2 / WSe2 prepared in step (4) is used as the working electrode and placed on the Cu 2+ : Ga 3+ :SeO3 2- In a solution of 1.6mmol / L:1.5mmol / L:4mmol / L, 0.5 mol / L sodium citrate is used as a complexing agent and 1.0 mol / L sodium sulfate is used as an electrolyte, HCl is used to adjust the pH value to between 1.8 and 2.0, and a single deposition is performed at -0.5V for 10s at a constant potential under stirring conditions, and the cumulative deposition is repeated 15 times to obtain a CuGaSe layer; (6) Prepare a selenium-modified bismuth oxide electrolyte and electrodeposit a Se-Bi2O3 layer: the electrolyte includes 4.85mmol / L bismuth nitrate, 0.9mmol / L sodium selenate, 0.2mmol / L acetic acid and deionized water, use the FTO / Au / MoSe2 / WSe2 / CuGaSe prepared in step (5) as the working electrode, a platinum mesh as the counter electrode, and a saturated calomel electrode as the reference electrode, deposit for 30-60min at a constant potential of -0.7V, dry it, take it out, and dry it in a 5vol.% oxygen-nitrogen mixed gas at a drying temperature of 70-80°C for 10-15h to finally obtain the desired optoelectronic composite material.

2. The optoelectronic composite material obtained by the method for preparing an optoelectronic composite material according to claim 1, characterized in that The optoelectronic composite material comprises, from bottom to top, an FTO substrate, a vapor-deposited Au layer, a MoSe2 coating, a WSe2 coating, a CuGaSe electrodeposited layer and a Se-Bi2O3 electrodeposited layer.

3. The optoelectronic composite material according to claim 2, characterized in that The thickness of MoSe2 is 70-80 μm.

4. The optoelectronic composite material according to claim 2, characterized in that The thickness of WSe2 is 100-130 μm.

5. The optoelectronic composite material according to claim 2, characterized in that The thickness of CuGaSe is 100-130 μm.

6. The optoelectronic composite material according to claim 2, characterized in that Se -The thickness of Bi2O3 is 90-120μm.

7. The use of the optoelectronic composite material as claimed in claim 2, characterized in that The composite material is used for photoelectrocatalytic reduction of carbon dioxide electrode.